Inhibitory Effect and Mechanism of Gallic Acid on α-Amylase and α-Glucosidase Activities - SHEN Heyu, LI Mengyang, AO Jingfang, WANG Jun, XU Huaide, LUO Anwei (Shipin Kexue, 2023)
In this study, the inhibitory effect and mechanism of gallic acid on α-amylase and α-glucosidase were investigated in terms of inhibitory rates, inhibition kinetics, ultraviolet (UV) spectra, fluorescence spectra, circular dichroism (CD) spectra, and molecular simulation. The results showed that gallic acid had a good inhibitory effect on α-amylase and α-glucosidase, with half maximum inhibitory concentrations (IC50) of (0.72 ± 0.01) and (0.59 ± 0.02) mmol/L, respectively, and inhibited α-amylase in a non-competitive manner and α-glucosidase in a mixed competitive-non-competitive manner. The results of UV spectroscopy and fluorescence quenching indicated that gallic acid statically quenched the fluorescence of the enzymes by altering the microenvironment around their aromatic amino acid residues. CD spectroscopy showed that gallic acid reduced the α-helix content and increased the β-sheet, β-turn and random coil contents of α-amylase and α-glucosidase, thus leading to changes in the enzymes’ conformation. The molecular docking results showed that gallic acid bound to α-amylase and α-glucosidase mainly through hydrogen bonds and hydrophobic interactions.